MANAJEMEN LEMBAGA PENDIDIKAN ISLAM (Analisis Terhadap Permendiknas RI. No. 24 Tahun 2007 Tentang Tandar Sarana dan Prasarana untuk SD/MI, SMP/MTS, dan SMA/MA) - Nona Kumala Sari (Sekolah Tinggi Agama Islam Sumatera Medan, 2019)
Facilities and infrastructure certainly need a touch of management theory and practice. Both in planning, implementation, and development. Unplanned facilities and infrastructure will certainly not go according to plan. In its implementation, the facilities and infrastructure will not function effectively and efficiently, in the sense that they do not hit the target as intended. Even in terms of development facilities and infrastructure that do not consider management aspects are certainly not able to look into the future, certainly not able to look at the needs of the community in the future. In this case the managers of educational institutions need to pay serious attention and involvement of management knowledge both in the provision of facilities and infrastructure, as well as in terms of maintenance even in the development of facilities and infrastructure.